Costs of Managerial Attention and Activity as a Source of Sticky Prices: Structural Estimates from an Online Market - Sara Ellison; Christopher M. Snyder; Hongkai Zhang (Center for Economic Studies and ifo Institute (CESifo), 2016)
We study price dynamics for computer components sold on a price-comparison website. Our fine-grained data—a year of hourly price data for scores of rival retailers—allow us to estimate a dynamic model of competition, backing out structural estimates of managerial frictions. The estimated frictions are substantial, concentrated in the act of monitoring market conditions rather than entering a new price. We use our model to simulate the counterfactual gains from automated price setting and other managerial changes. Coupled with supporting reduced-form statistical evidence, our analysis provides a window into the process of managerial price setting and the microfoundation of pricing inertia, issues of growing interest in industrial organization and macroeconomics.
Keywords: L11; C73; D21; L81; 330